2021
DOI: 10.1002/er.7130
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage characteristics of bio‐based porous carbons of different origin: A comparative review

Abstract: Summary Activated carbons (ACs) from biomass sources have attracted attention due to their superior properties including, easy preparation, abundant raw materials, ready availability, low cost, low mass density, high specific surface area and micropore volume, fast and reversible kinetics, structural diversity, and sustainable regeneration. Due to their tunable aspects, bio‐derived ACs are among the most promising materials for the storage of hydrogen. In this contribution, the comparative evaluation of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 83 publications
(633 reference statements)
0
13
0
Order By: Relevance
“…However, the production of ACs from these finite resources is expensive, requires intensive regeneration, and cannot serve a high and increasing demand for global AC consumption 12 Thus, a plethora of research have focused on the synthesis of ACs from sustainable resources, such as biomass/agricultural wastes 14 , 16 , 24 , 35 38 , municipal wastes 30 , 32 , 39 , and industrial wastes 40 42 . The production of AC from wastes is not only a sustainable process but also an environmentally friendly and a cost-effective strategy based on the reduction of waste disposal and the low production cost of AC 43 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of ACs from these finite resources is expensive, requires intensive regeneration, and cannot serve a high and increasing demand for global AC consumption 12 Thus, a plethora of research have focused on the synthesis of ACs from sustainable resources, such as biomass/agricultural wastes 14 , 16 , 24 , 35 38 , municipal wastes 30 , 32 , 39 , and industrial wastes 40 42 . The production of AC from wastes is not only a sustainable process but also an environmentally friendly and a cost-effective strategy based on the reduction of waste disposal and the low production cost of AC 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the storage of hydrogen remains challenging. Currently, the hydrogen storage can be accomplished through (i) compressed gas, (ii) cryo‐liquid, and (iii) solid storage media, that is, metal hydrides, complex hydrides, and/or carbon materials 50,51 . These methods are widely used and have attractive hydrogen storage qualities 52,53 .…”
Section: Need For Hydrogen Energymentioning
confidence: 99%
“…Activated carbon derived from biomass as a CO 2 adsorbent is consistent with sustainable development and is favored by many researchers 19 . As a nut food with a huge consumer market, macadamia nuts have a large output in China, and macadamia nutshells are the main by‐product in the production process 20 . The annual production of macadamia nutshells is huge, but there is no efficient way to use them, only as crop waste disposal.…”
Section: Introductionmentioning
confidence: 95%
“…19 As a nut food with a huge consumer market, macadamia nuts have a large output in China, and macadamia nutshells are the main by-product in the production process. 20 The annual production of macadamia nutshells is huge, but there is no efficient way to use them, only as crop waste disposal. Research analysis found that the carbon content of the macadamia nutshell is high and the ash content is extremely low, so the macadamia nutshell is an ideal precursor.…”
Section: Introductionmentioning
confidence: 99%